Optimizing HR Management to Improve Employee Performance in North Sumatera Public Works Office - Horia Siregar; Nur’ain Harahap; Padilah Rahmi Lubis; Lutvi Noviyanti; Mahira Zhubda Rangkuti (International Forum of Researchers and Lecturers, 2025)
Human resource management (HR) in the government sector, especially in the Public Works and Spatial Planning Agency (PUPR) of North Sumatra Province, has a crucial role in determining the effectiveness and efficiency of public services. However, HR management in government agencies still faces various challenges, such as complex bureaucracy, lack of innovation, and employee competency gaps. This study aims to analyze the challenges in HR management and the factors that influence employee performance in order to formulate strategies for optimizing HR management in the government sector. Using qualitative research methods, data were obtained through interviews, document studies, and literature reviews. The results of the study indicate that a rigid personnel system, lack of competency development, and a recruitment and promotion system that is not fully performance-based are the main factors that hinder the effectiveness of employee work. Therefore, reforms are needed in the HR management system, such as improving the recruitment, promotion, and rotation mechanisms of employees, strengthening competency development policies through adaptive training programs, and implementing a performance evaluation system based on objectivity and transparency. With this optimization strategy, it is hoped that employee performance at the PUPR Office of North Sumatra Province can improve, so that public services become more effective and professional.